NAIRU: Incomes Policy and Inflation - Fabiani, Silvia (OECD Economics Department Working Papers, 1997)
Italy has been one of the few industrial countries resorting to incomes policy in the current decade. Many Italian observers have attributed to this policy the remarkable slowdown in wage and price inflation. However, no apparent progress has been made concerning labour market unbalances, as the unemployment rate remains 4 percentage points above the already high level inherited from the 80s. This paper analyses this experience: it looks at the evidence of changes in the bargaining structure stemming from the incomes policies agreements, discusses their possible long run impact in terms of NAIRU and features of the inflationary process, presents a quantitative assessment of the specific contribution of those agreements to the inflation outcome. The analysis is carried out by looking at the presence of structural breaks in an aggregate-wage equation and resorting to counterfactual simulations of a large macroeconomic model (the Bank of Italy quarterly model). The empirical results ...